Experimental Analysis of Heat Transfer Enhancement in Double Tube Heat Exchanger with Air Injection - Flayh, Roasi Abd El Raheem; Flayh, Ayser Muneer (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Double-tube heat exchangers are frequently utilized due to their low assemble and maintenance cost. In order to extract a large amount of thermal energy at minimum time and cost, an active method of air bubble injection was developed to increase the heat transfer rate through vertical double-tube heat. The current study explores the influence of air bubble injection on the thermal efficiency of vertical double tubes at counter flow. There were two main modes were adopted to conduct the experiments. The first mode was done without air injection (single phase). In the second mode, the air was injected into the heat exchanger’s outer tube through a ring tube into the annular side of the heat exchanger. Cold water flow rate was ranged as (3, 3.5, 4, 4.5, 5 LPM) with 17°C temperature, while hot water was kept constant at (3LPM) with inlet temperature 70°C, and air was injected with (0.5, 1, 1.5, 2 LPM). Results found that overall heat transfer was enhanced by (41%), NTU (49%), effectiveness enhanced by (44%) and Nusselt number (45.2%).